1993
DOI: 10.1542/peds.91.1.253
|View full text |Cite
|
Sign up to set email alerts
|

Alternative Child Care in France: Advances in the Study of Motor, Interactive, and Social Behaviors of Young Children in Settings Allowing Them to Move Freely in a Group of Peers

Abstract: This paper reports new data on the emergence and development from the 9th to 19th month of age of motor, interactive, and social behaviors of 17 children with peers in a milieu that allows the "conquest" of the third dimension of space without limitation of their motor activity. Their motor skills and social behaviors appear more precocious and complex than previously indicated by scientific publications, clinical observations, and developmental scales. 1. The motor skills that allow the "conque… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

1996
1996
2005
2005

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 11 publications
(2 citation statements)
references
References 0 publications
0
2
0
Order By: Relevance
“…Thus, "opportunities for practice, encouragement, instruction, and the ecology (setting) of the environment itself, all play important roles in the degree to which fundamental movements patterns develop." (17) In this way it should be found out which were the conditions in the day-care centers that helped the Besides, the internal spaces of the 3 daycare centers are organized in corner activities such as to favor the infantile development (18)(19) . Then, it was observed that children two to three years' old seem to present a greater number of suspects.…”
Section: -2003mentioning
confidence: 99%
“…Thus, "opportunities for practice, encouragement, instruction, and the ecology (setting) of the environment itself, all play important roles in the degree to which fundamental movements patterns develop." (17) In this way it should be found out which were the conditions in the day-care centers that helped the Besides, the internal spaces of the 3 daycare centers are organized in corner activities such as to favor the infantile development (18)(19) . Then, it was observed that children two to three years' old seem to present a greater number of suspects.…”
Section: -2003mentioning
confidence: 99%
“…Therefore, for toddlers, bodily games may have greater social importance than games with small objects. Montagner et al (1993) showed in their longitudinal study, how over a period from nine to nineteen months of age, toddlers not only developed their motor skills but also their affiliative and cooperative behaviours in a milieu that allowed moving in space with no limitation. The toddlers shared games that were fun and long-lasting with very little aggressiveness or self-centred behaviours.…”
Section: Objects Spaces and Playing Togethermentioning
confidence: 99%